Can pedicled TRAM flap be a satisfying alternative to free TRAM in developing countries? – a systematic review and meta-analysis. Issue 6 (1st November 2020) - Vania, Rachel; Pranata, Raymond; Berfan, Albertus; Budiman, Budiman
Abstract: Background: Breast reconstruction can ease the psychological burden in breast cancer patients that have undergone mastectomy. The aim of our study is to collect the latest evidences to summarize whether pedicled TRAM (pTRAM) is non-inferior in terms of patient satisfaction and complications to free TRAM (fTRAM) so that it may be used in region with limited resources. Methods: We performed a comprehensive search on studies that compared pTRAM and fTRAM flap from several databases. Results: There are six studies included. Despite the diversity among the correspondents, all studies demonstrated no difference between the two groups regarding patient overall satisfaction. However, two studies found that pTRAM had lower abdominal well-being score, three found higher abdominal related morbidity, while fTRAM had a higher overall cost. Pooled mean difference was not significant on all BREAST-Q subscales, meaning that pTRAM and fTRAM has a similar outcome. Conclusion: Although pTRAM is non-inferior in terms of satisfaction to fTRAM, it is associated with a more frequent complication. It may be used in developing countries that lack facilities and limited by cost. However, pTRAM should be done by experienced surgeons to minimize the risk of complications.